The Effect of Use Of Blended Learning OnMotivation To Learn Mathematics With Collaborative Learning Media Whatsapp And ZoomIn Class X Mipa 3 Upt Sma Negeri 1 Parepare - Musdalifa Ibrahim (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to determine whether or not there is an effect of using the blended learning strategy in Math online learning via WhatsApp and zoom. This research method uses a qualitative descriptive method. The data in this study were collected through observation, interviews, and documentation. The results obtained indicate that online learning using the WhatsApp and zoom application with the blended learning strategy during the Covid-19 pandemic can provide more enjoyable learning so as to increase student enthusiasm and activity. The conclusion obtained from this study is that the use of the blended learning strategy affects online math learning via WhatsApp and zoom can be an alternative in online biology learning via Whatsapp in conditions that do not allow face-to-face learning